Analysis of the Challenges and Solutions in Delivering and Ensuring the Quality of Desalinated Water to the Consumer: An Applied Study on the Saudi Water Authority (International Journal of Financial, Administrative and Economic Sciences, 2024)
The study aimed to explore solutions to challenges related to (improving infrastructure, rectifying logistical system deficiencies, and enhancing quality control efficiency) in the delivery and assurance of desalinated water quality to consumers, with a focus on the Saudi Water Authority. The study population consisted of employees at the Saudi Water Authority in Saudi Arabia. Due to the difficulty of conducting a comprehensive survey of the entire population, a simple random sampling method was used by distributing a questionnaire on social media platforms associated with the employees. The sample included 402 participants, and the study adopted a descriptive analytical approach to data analysis. The study's findings revealed a statistically significant positive impact of solutions addressing infrastructure improvements, logistical system rectifications, and quality control efficiency on the enhancement of desalinated water quality for consumers. The study recommended providing financial resources and logistical and technical support to enhance the Saudi Water Authority’s capacity to achieve the goals of Vision 2030, and improving the infrastructure to increase the productivity and efficiency of the authority in attaining the highest performance levels.
Keywords: Water Desalination; Water Quality; Saudi Water Authority; Infrastructure; Logistical System; Quality Control